WORKSHOP ANIMASI dan MULTIMEDIA EDUKATIF untuk GURU SD - Sundahry sundahry; Yogi Irdes Putra; Nur Afriyanti Daulay (GERAKAN EDUKASI DAN MASYARAKAT NUSANTARA, 2025)
The rapid development of digital technology in education requires teachers to integrate multimedia into more innovative and engaging learning processes. Educational animation and multimedia have proven effective in increasing students’ learning interest, facilitating the understanding of abstract concepts, and creating more interactive learning experiences at the elementary level. However, observations show that many elementary school teachers still lack the skills to create educational multimedia content that matches the characteristics of young learners. This limitation affects the variety of learning media used and leads to low student engagement in classroom activities. This community service program was carried out through three main stages. The first stage involved an initial survey to identify participants’ profiles, their technological skills, and specific needs related to multimedia learning media development. The findings served as the basis for designing a workshop that matched participants’ needs. The second stage was a two-day intensive workshop consisting of four main sessions: introducing the concepts of educational animation and multimedia, hands-on training using Powtoon, Canva, and Animaker, instruction on effective multimedia content design principles, and guided practice in creating animation projects relevant to each teacher’s subject.